A Review On Security Issues In Cloud Computing (International Journal of Engineering and Computer Science, 2017)
The data security in cloud is an important issue. The important data can be stored in cloud and the security of that data is totally dependent on cloud. The data might be uncovered by the malicious third party user because of wireless connection between client and cloud without proper authentication and protection. In this paper we figure out the different security  issues with the cloud . When the data is stored in cloud the data should be properly managed and cloud have to provide a proper security to the data.  In this paper discussing the different type of issues with the cloud and also possible policies are mentioned here that we can take care of those issues while discussing about the security provided by the cloud.